Primary bilateral corneal T cell lymphoma in a horse. (13th December 2021) - Opgenorth, T. A.; Monk, C. S.; Brooks, D. E.; Ramos, R. R.; Craft, S. L.; Plummer, C. E.
Summary: A 5‐year‐old Belgian Warmblood gelding presented for evaluation of increased opacity in both eyes. Initial ophthalmic examination revealed bilateral mild blepharospasm, multifocal axial and dorsal anterior stromal corneal opacities with mild axial mid‐stromal haze and oedema, and superficial, branching corneal vascularisation. A presumptive diagnosis of bilateral immune‐mediated keratitis (IMMK) was made. The lesions progressed despite 2 years of exhaustive options for medical management. Surgical intervention in the left eye with lamellar keratectomy and ocular surface reconstruction with amnion membrane transplantation was elected. The keratectomy specimen was submitted for histopathology and was consistent with immune‐mediated keratitis. When surgical intervention in the right eye was performed, histopathology revealed sheets of atypical round cells with a high mitotic index. Immunohistochemistry from both the left and right specimens had immunoreactivity to CD3 antibodies. An amended diagnosis of bilateral T cell lymphoma was made. The patient recovered well from surgery, and there have been no signs of recurrence or systemic involvement following surgical intervention. This is a unique case of primary corneal T cell lymphoma in a horse. Prior to electing surgical management, the patient received topical immunomodulating medications including cyclosporine and tacrolimus for significant lengths of time. Both chronic inflammation and chronic administration of immunosuppressive agents are associated with neoplastic transformation. Surgical intervention provides both a diagnostic sample and therapeutic relief.